FREQUENCY OF HELICOBACTER PYLORI (HP) INFECTION IN CHILDREN WITH RECURRENT ABDOMINAL PAIN (RAP): Helicobacter Pylori Infection in Children - Mahmud, Shahid; Shah, Syed Awais Ul Hassan; Ali, Salman (Pakistan Armed Forces Medical Journal, 2015)
Objective: To study the frequency of Helicobacter Pylori (HP) infection among children with recurrent abdominal pain (RAP)Study Design: Cross-sectional comparative study.Place and Duration of Study: Military Hospital (MH), Rawalpindi from December 2011 to February 2012.Patients and Methods: One hundred children of either gender aged 2 to 12 years presenting with RAP were tested for HP at Paediatric OPD MH, Rawalpindi who consented to participate in the study. Those children who tested positive for Helicobacter Pylori Stool Antigen Test (HPSAT) were labeled as those having Hp infection. The stool assay was performed using the HpSAT kit and the socio-demographic and clinical profiles of children were associated.Results: Out of 100 children included in the study HpSAT was positive in 38% children. Frequency of Hp infection was significantly associated with source of drinking water (p = 0.014), socioeconomic status (p = 0.001) and positive family history of dyspepsia (p= 0.023). While age and gender have no significant association with HP infection.Conclusion: Hp infection is very common in children presenting with RAP in our Paediatric OPD. Children with family history of dyspepsia, from low socioeconomic class and those drinking filtered water are at greater risk for HP infection. It is recommended that children from other populations in our country should also be tested in their medical health facilities in order to have a wider analysis of this problem in our setup.